The Association Between Testosteron Levels and Relationship Quality in Reproductive Aged Couples - Ganis Siregar, Fidel (KnE Medicine, 2016)
Couple relationship is often interfered by disorder in sexual activities. Most of the problems are in women than men. One of the main factor tha contributed to sexual function are sex hormones. Sex hormones selectively responsive to sexual incentives inducing a neurochemical state that favourable to sexual response. Androgens play an important role in sexual desire, arousal, orgasm and satisfaction by interacting with receptors in the hypothalamus, together with the dopaminergic, serotoninergic and opiatergic path, and the receptor genitals. Testosterone, molecular weight of 288.41 Dalton, is one of sex steroid hormones. It is the main androgenic hormone produced by the interstitial cells (Leydig). However, testosterone is an important precursor for the production of estradiol in the target tissue. Both testosteron and estrogen may affect sexual arousal. Decrease of testoterone in men is also related to declines in sexual desire, which can be restored with testosteron administration. Therefore, adding testosteron to estrogen in sexual disorder may be benefited. However, this practice was not widely use. Furhter sutdy is needed to assess its long term side effect.